Preparation method of polyurethane binder for silicon negative electrode
By preparing a polyurethane binder, using materials such as polyether diol and aminosilane coupling agent, the powdering problem caused by volume expansion of the silicon negative electrode is solved, and the cycle stability and rate performance of lithium-ion batteries are significantly improved.
Patent Information
- Application Number
- CN202311224480.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-03-21
AI Technical Summary
The silicon negative electrode in lithium-ion batteries causes the active material to powder due to the stress caused by volume expansion, and loses electrical contact, resulting in low cycle stability and short battery life.
A polyether diol and diisocyanate were mixed with a catalyst and a solvent for prepolymerization, followed by addition of a chain extender and an aminosilane coupling agent for polymerization, and a polyurethane binder capable of enhancing the adhesion between active materials, conductive agents and current collectors was prepared.
This binder improves the rate performance of lithium ions by forming ether oxygen bonds, and forms silicon oxygen bonds through aminosilane coupling agents, enhancing the bonding cooperation between the binder and the silicon negative electrode, improving cycle stability and battery life.
Smart Images

Figure BDA0004461803640000051 
Figure BDA0004461803640000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for preparing a polyurethane binder for a silicon negative electrode. Background Art
[0002] The performance of lithium-ion batteries depends greatly on their positive and negative electrode materials. In order to meet the requirements of various fields for high-capacity, high-energy, and high-power lithium-ion batteries, researchers have invested a lot of energy in studying negative electrode materials with high theoretical capacity, such as silicon, germanium, and tin. Among them, silicon materials are low in cost and abundant in reserves. When used as negative electrode materials, the lithium insertion / extraction potential is relatively low (~0.4V vs. Li / Li + ), and its theoretical specific capacity also ranks first among all negative electrode materials. When fully embedded with lithium, the theoretical capacity can reach 4200mAh / g, which is an order of magnitude higher than that of traditional graphite negative electrode.
[0003] However, in actual use, the silicon negative electrode will produce drastic volume changes during the process of lithium insertion and extraction. After this repeated volume change, due to the effect of intrinsic stress, the silicon negative electrode active material will be powdered and separated from the conductive agent and current collector in the electrode. After losing electrical contact, the negative electrode active material will be inactivated, the material's cycle stability is not high, and the battery life is also short.
[0004] In order to solve the problem of volume expansion during the actual use of silicon negative electrodes, the binder can be improved to improve the adhesion of the electrode material. Only binders with high bonding strength can withstand the stress caused by the volume expansion of silicon negative electrodes and ensure effective contact between active materials, conductive agents and collectors, thereby minimizing capacity attenuation and improving cycle life. However, so far, most binders are not compatible in terms of capacity characteristics and cycle characteristics. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a polyurethane binder for silicon negative electrode in order to solve the above technical problems. The obtained binder can effectively enhance the adhesion between active materials, conductive agents and current collectors, and improve the cycle performance and rate performance of silicon negative electrode materials for lithium ion batteries.
[0006] The preparation method of the polyurethane binder for silicon negative electrode in the technical solution of the present invention comprises mixing polyether diol and diisocyanate, adding a catalyst and a solvent for prepolymerization, and then adding a chain extender and an aminosilane coupling agent for polymerization.
[0007] The polyether diol is used as the soft segment of the polyurethane binder, in which the ether oxygen bond (-O-bond) has a strong electronegativity, and lithium ions can be adsorbed near the oxygen atom, which is beneficial to the transmission of lithium ions in the binder, thereby improving the rate performance of the lithium ion battery. Further, the polyether diol is one or more of polytetrahydrofuran diol, polyoxypropylene diol, tetrahydrofuran-oxypropylene copolymer diol, and the number average molecular weight is 1000-4000; preferably polytetrahydrofuran diol.
[0008] Further, the polyether diol is vacuum dehydrated at 100-120° C. for 1.0-2.0 h.
[0009] Furthermore, the diisocyanate is one or more of 4,4'-diphenylmethane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, and toluene diisocyanate, preferably 4,4'-diphenylmethane diisocyanate.
[0010] Furthermore, the molar ratio of diol to diisocyanate is 1.0:1.0-4.0.
[0011] Furthermore, the catalyst is an amine catalyst or an organic metal catalyst, which is listed as one or more of N,N-dimethylcyclohexylamine, triethanolamine, dibutyltin dilaurate, and stannous octoate.
[0012] Furthermore, the mass of the catalyst is 0.3-1.0% of the total mass of the diol and the diisocyanate.
[0013] Furthermore, the solvent is one or more of N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide, and xylene.
[0014] Preferably, the solvent is passed through a dry molecular sieve to remove water before use.
[0015] Furthermore, the mass of the solvent is 3 to 5 times the sum of the mass of the diol and the diisocyanate.
[0016] Furthermore, the chain extender is one or more of ethylenediamine, 1,4-butanediol, and diethylene glycol.
[0017] Furthermore, the aminosilane coupling agent contains one or two nitrogen atoms in the molecular chain, which can be one or more of 3-aminopropyltrimethoxysilane KH540, γ-aminopropyltriethoxysilane 550, γ-aminoethylaminopropyltrimethoxysilane, and vinylbenzylaminoethylaminopropyltrimethoxysilane.
[0018] Aminosilane coupling agent is used as a partial chain extender to produce covalent crosslinking with the prepolymer of the polyurethane binder, and finally form silicon-oxygen bonds in the polyether polyurethane, which is beneficial to enhance the bonding effect between the binder and the silicon negative electrode and improve the cycle stability.
[0019] Furthermore, the mass ratio of the chain extender to the aminosilane coupling agent is 8.0-9.0:1.0-2.0.
[0020] Furthermore, the total mass of the chain extender and the aminosilane coupling agent is 5-10% of the total mass of the diol and the diisocyanate.
[0021] Furthermore, the temperature of the prepolymerization and polymerization reactions are both 70-100° C., and the time is 2.0-4.0 hours.
[0022] Preferably, after the polymerization reaction, vacuum is applied to remove air bubbles.
[0023] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0024] (1) The present invention uses polyether diol as the soft segment and adds an aminosilane coupling agent as a partial chain extender. The resulting binder can effectively enhance the adhesion between the active material, the conductive agent and the current collector, and improve the cycle performance and rate performance of the lithium ion battery;
[0025] (2) The ether oxygen bond (-O- bond) in the molecular chain of polyether diol has a strong electronegativity. + It can be adsorbed near oxygen atoms, which is beneficial to the transmission of lithium ions in the binder and helps to improve the rate performance of lithium-ion batteries;
[0026] (3) The aminosilane coupling agent, as a partial chain extender, produces covalent crosslinking with the prepolymer of the polyurethane binder, and finally forms a silicon-oxygen bond in the polyether polyurethane, which is beneficial to enhance the bonding between the binder and the silicon negative electrode and improve the cycle stability;
[0027] (4) Using polyether diol as the soft segment and aminosilane coupling agent as a partial chain extender, the electrochemical performance of the battery is improved through a simple method, which is suitable for industrial application. DETAILED DESCRIPTION
[0028] The technical scheme of the present invention is further described below by specific embodiments. It should be understood that the specific embodiments described herein are only used to help understand the present invention and are not intended to be used for specific limitations of the present invention. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.
[0029] Example 1
[0030] The method for preparing the polyurethane binder for silicon negative electrode of this embodiment comprises the following steps:
[0031] (1) Polytetrahydrofuran diol 2000 was vacuum dehydrated at 110° C. for 1.5 h, the vacuum dehydrated polytetrahydrofuran diol (15 g, 7.5 mmol) was mixed with 4,4'-diphenylmethane diisocyanate (7.5 g, 30 mmol), 0.15 g of dibutyltin dilaurate and 80 g of xylene (dried with molecular sieve to remove water) were added, stirred evenly, and the temperature was raised to 80° C. for reaction for 2 h to obtain a prepolymer;
[0032] (2) Add 1.8 g of ethylenediamine and 0.2 g of aminosilane coupling agent KH550 to the prepolymer, react at 80° C. for 1 h, and evacuate to remove bubbles to obtain a polyurethane binder for silicon negative electrode.
[0033] Example 2
[0034] The method for preparing the polyurethane binder for silicon negative electrode of this embodiment comprises the following steps:
[0035] (1) Polyoxypropylene glycol 2000 was vacuum dehydrated at 110° C. for 1.5 h, the vacuum dehydrated polyether diol (15 g, 7.5 mmol) was mixed with toluene diisocyanate (7.5 g, 30 mmol), 0.15 g of dibutyltin dilaurate and 80 g of xylene (dried with molecular sieve to remove water) were added, stirred evenly, and the temperature was raised to 85° C. for reaction for 1.5 h to obtain a prepolymer;
[0036] (2) Add 1.8 g of 1,4-butanediol and 0.2 g of vinylbenzylaminoethylaminopropyltrimethoxysilane to the prepolymer, react at 90° C. for 1 h, and evacuate to remove bubbles to obtain a polyurethane binder for silicon negative electrode.
[0037] Example 3
[0038] The method for preparing the polyurethane binder for silicon negative electrode of this embodiment comprises the following steps:
[0039] (1) Polytetrahydrofuran diol 2000 was vacuum dehydrated at 110° C. for 1.5 h, the vacuum dehydrated polytetrahydrofuran diol (15 g, 7.5 mmol) was mixed with 4,4'-diphenylmethane diisocyanate (7.5 g, 30 mmol), 0.18 g of dibutyltin dilaurate and 90 g of xylene (dried with molecular sieve to remove water) were added, stirred evenly, and the temperature was raised to 80° C. for reaction for 2 h to obtain a prepolymer;
[0040] (2) Add 1.6 g of 1,4-butanediol and 0.4 g of aminosilane coupling agent KH550 to the prepolymer, react at 80° C. for 1 h, and evacuate to remove bubbles to obtain a polyurethane binder for silicon negative electrode.
[0041] Example 4
[0042] The difference between this embodiment and embodiment 1 is that in step (1), polytetrahydrofuran diol 2000 is vacuum dehydrated at 110° C. for 1.5 h, the vacuum dehydrated polytetrahydrofuran diol (15 g, 7.5 mmol) is mixed with 4,4'-diphenylmethane diisocyanate (5.6 g, 22.5 mmol), 0.15 g of dibutyltin dilaurate and 80 g of xylene (dried with molecular sieve to remove water) are added, stirred evenly, and the temperature is raised to 80° C. for reaction for 2 h to obtain a prepolymer.
[0043] Example 5
[0044] The difference between this embodiment and embodiment 1 is that in step (1), polytetrahydrofuran diol 2000 is vacuum dehydrated at 110° C. for 1.5 h, the vacuum dehydrated polytetrahydrofuran diol (15 g, 7.5 mmol) is mixed with 4,4'-diphenylmethane diisocyanate (3.75 g, 15 mmol), 0.15 g of dibutyltin dilaurate and 80 g of xylene (dried with molecular sieve to remove water) are added, stirred evenly, and the temperature is raised to 80° C. for reaction for 2 h to obtain a prepolymer.
[0045] Example 6
[0046] The difference between this embodiment and embodiment 1 is that in step (2), 1.9 g of ethylenediamine and 0.1 g of aminosilane coupling agent KH550 are added to the prepolymer, reacted at 80° C. for 1 h, and vacuumed to remove bubbles to obtain a polyurethane binder for silicon negative electrode.
[0047] Example 7
[0048] The difference between this embodiment and embodiment 1 is that in step (2), 1.5 g of ethylenediamine and 0.5 g of aminosilane coupling agent KH550 are added to the prepolymer, reacted at 80° C. for 1 h, and vacuumed to remove bubbles to obtain a polyurethane binder for silicon negative electrode.
[0049] Comparative Example 1
[0050] The preparation method of the polyurethane binder for silicon negative electrode in this comparative example comprises the following steps:
[0051] (1) Polyethylene glycol 2000 was vacuum dehydrated at 110° C. for 1.5 h, the vacuum dehydrated polyethylene glycol (15 g, 7.5 mmol) was mixed with 4,4'-diphenylmethane diisocyanate (7.5 g, 30 mmol), 0.15 g of dibutyltin dilaurate and 80 g of xylene (dried with molecular sieve to remove water) were added, stirred evenly, and the temperature was raised to 80° C. for reaction for 2 h to obtain a prepolymer;
[0052] (2) Add 1.8 g of ethylenediamine and 0.2 g of aminosilane coupling agent KH550 to the prepolymer, react at 80° C. for 1 h, and evacuate to remove bubbles to obtain a polyurethane binder for silicon negative electrode.
[0053] Comparative Example 2
[0054] The difference between this comparative example and Example 1 is that in step (2), 2.0 g of ethylenediamine is added to the prepolymer, reacted at 80° C. for 1 h, and vacuumed to remove bubbles to obtain a polyurethane binder for silicon negative electrode.
[0055] Comparative Example 3
[0056] The difference between this comparative example and Example 1 is that in step (2), 1.8 g of ethylenediamine and 0.2 g of silane coupling agent KH570 are added to the prepolymer, reacted at 80° C. for 1 h, and vacuumed to remove bubbles to obtain a polyurethane binder for silicon negative electrode.
[0057] Nano silicon powder, acetylene black and the above polyurethane binder were mixed in a mass ratio of 70:10:20, and an appropriate amount of N-methylpyrrolidone was added. The resulting slurry was evenly coated on the current collector copper foil and dried at 110°C for 12 h under vacuum. The dried copper foil was then cut into discs with a diameter of 14 mm and compacted at 20 MPa for 40 s to obtain a battery negative electrode sheet. Finally, the negative electrode sheet, lithium sheet, separator (Celgard2400) and electrolyte were assembled into a CR2032 button battery in a glove box filled with argon atmosphere. The electrochemical properties were tested, and the test results are shown in Table 1.
[0058] Table 1 Lithium-ion battery electrochemical performance data
[0059]
[0060]
[0061] The polyurethane binders obtained in Examples 1-5 are assembled into lithium-ion batteries with excellent electrochemical properties. In Example 6, too little aminosilane coupling agent is added when preparing the polyurethane binder, and the degree of reaction with the polyurethane prepolymer is low in the chain extension stage, which may reduce the force with the silicon negative electrode during the charge and discharge process, thereby affecting its cycle stability; in Example 7, too much aminosilane coupling agent is added when preparing the polyurethane binder. The silane coupling agent with a larger volume will result in a lower molecular weight of the final polyurethane, thereby resulting in weaker bonding force. Too much small molecule silane coupling agent will cause capacity reduction and faster attenuation; Comparative Example 1 uses polyethylene glycol 2000 as the soft segment of the polyurethane binder, which does not contain -O- bonds, reduces the lithium ion transmission rate, and reduces the electrochemical performance of the battery; In Comparative Example 2, no aminosilane coupling agent is added when preparing the polyurethane binder, resulting in a decrease in the bonding between the binder and the silicon negative electrode, thereby affecting the cycle stability; In Comparative Example 3, the silane coupling agent added when preparing the polyurethane binder does not contain an amino group, and it is difficult to react with the polyurethane prepolymer, and at the same time causes the molecular weight of the polyurethane to decrease, thereby reducing the cycle stability.
[0062] Finally, it should be noted that the specific embodiments described herein are merely examples of the spirit of the present invention, and are not intended to limit the implementation methods of the present invention. Those skilled in the art of the present invention may make various modifications or supplements to the described embodiments or replace them in similar ways. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A method for preparing a polyurethane binder for a silicon negative electrode, characterized in that: The preparation method comprises the steps of mixing polyether diol and diisocyanate, adding a catalyst and a solvent to carry out prepolymerization, and then adding a chain extender and an aminosilane coupling agent to carry out polymerization reaction.
2. The preparation method according to claim 1, characterized in that: The polyether diol is one or more of polytetrahydrofuran diol, polyoxypropylene diol and tetrahydrofuran-oxypropylene copolymer diol, and has a number average molecular weight of 1000-4000.
3. The preparation method according to claim 1 or 2, characterized in that: The polyether diol is vacuum dehydrated at 100-120°C for 1.0-2.0h.
4. The preparation method according to claim 1, characterized in that: The molar ratio of diol to diisocyanate is 1.0:1.0-4.
0.
5. The preparation method according to claim 1, characterized in that: The mass of the catalyst is 0.3-1.0% of the total mass of the diol and the diisocyanate.
6. The preparation method according to claim 1, characterized in that: The mass of the solvent is 3 to 5 times the sum of the mass of the diol and the diisocyanate.
7. The preparation method according to claim 1, characterized in that: Aminosilane coupling agents contain one or two nitrogen atoms in their molecular chains.
8. The preparation method according to claim 1, characterized in that: The mass ratio of the chain extender to the aminosilane coupling agent is 8.0-9.0:1.0-2.
0.
9. The preparation method according to claim 1, characterized in that: The total mass of the chain extender and the aminosilane coupling agent is 5-10% of the total mass of the diol and the diisocyanate.
10. The preparation method according to claim 1, characterized in that: The temperature of the prepolymerization and polymerization reactions is 70-100°C, and the time is 1.0-4.0h.